212 Preventing blindness for patients with optic disc swelling: improving care using transformative new technology. Issue 6 (27th May 2022) - Braithwaite, Tasanee; Wu, Kit; Saunders, Katherine; Teo, James; Yorke, Richard; Moosai, Shivir; Brex, Peter; O'Sullivan, Eoin
Abstract : Introduction: Optic disc swelling (ODS) is a non-specific sign with clinical consequences ranging from benign to irreversible blindness. It is often a challenge to manage: patients present to different specialities and there is no unifying clinical pathway. Objectives/Aims: 1. to identify all patients presenting to King's College Hospital with ODS using a translational informatics digital platform (Cogstack); 2. to develop an electronic care pathway with an integrated decision support tool. Method: We used a digital translational informatics platform called Cogstack, developed in-house by King's College London, to search 1.4billion EPR data files during a 12-week period. We engaged an MDT team to developed a clinical decision support tool, containing 'red flag' symptoms and signs for patients presenting with ODS. Results: Cogstack identified 407 patients with ODS in a 12-week period. Of these, 15% were new cases, 24% were not seen or referred to (neuro)/ophthalmology. The care pathway ensured that patients received timely investigation and initial management facilitated by transformative new technology. This translated into saving time, standardising care and enhanced patient safety. Conclusion: This technology-facilitated care pathway provides a proof of concept for other institutions. Its development supports the topical agenda of NHS improvement, to 'Get it Right First Time', and the aim to deliver a value-based healthcare. kitwu@doctors.org.uk